Water Inrush Risk Assessment Based on AHP and Advance Forecast Approach: A Case Study in the Micangshan Tunnel - Tao Song; Jun Zeng; Jiaji Ma; Chunchi Ma; Tianbin Li; Tao Xia (Advances in Civil Engineering)
Water inrush is a serious geological disaster in tunnel. For the effective prevention and control of the occurrence of water inrush, a static-dynamic water inrush risk assessment method is proposed by considering the Micangshan tunnel as an example. First, four possible types of water inrush phenomenon are identified based on the geological and hydrogeological conditions of the tunnel: water inrush in water-bearing cracks, fault fracture zones, karst pipelines, and karst caves. Next, evaluation indexes that affect water inrush are determined. By combining the index weight value calculated by analytic hierarchy process (AHP) with the index quantitative value, the static water inrush disaster evaluation model is established, which provides a basis for tunnel design. Finally, with the combination of the static evaluation model and advanced forecast method, a dynamic risk prediction method of water inrush is established, which provides guidance for safe construction. The results confirm that the proposed method is a reliable theoretical basis for early assessment and prediction of tunnel water inrush disasters.